ALGORITHM FOR IMPROVING FEEDING RATES OF INDUSTRIAL WELDING ROBOT TA 1400 IN COMBINATION WITH A TURNTABLE FRAME - Mai, Ngoc Anh; Duong, Xuan Bien (Journal of Computer Science and Cybernetics, 2020)
An algorithm for improving feeding rates of industrial welding robot TA 1400 of Panasonic with 6 degrees of freedom is presented. The kinematics and dynamics of the robot are calculated on MATLAB software. The proposed algorithm for improving feeding rates is mathematically analyzed and the performance of the system is evaluated in a simulation environment. The simulation results are used for proving the efficiency of the solution. Based on the achieved results, the algorithm can be applied for reducing time and improving the productivity of other industrial robots in the future